Ameliorative Effects of Isoeugenol and Eugenol against Impaired Nerve Function and Inflammatory and Oxidative Mediators in Diabetic Neuropathic Rats - Khalid M. Alharthy; Mohamed F. Balaha; Sushma Devi; Ali Altharawi; Hasan S. Yusufoglu; Rana M. Aldossari; Aftab Alam; Viviana di Giacomo (Biomedicines, 2023)
Diabetic polyneuropathy is characterized by structural abnormalities, oxidative stress, and neuroinflammation. The current study aimed to determine the antinociceptive effects of isoeugenol and eugenol and their combinations in neuropathic pain resulting from streptozotocin (STZ)-induced diabetes and neuroinflammation. Female SD rats were categorized into normal control, diabetic control, and treatment groups. On the 28th day and 45th day, behavioral studies (allodynia and hyperalgesia) were performed to analyze the development and protection of diabetic polyneuropathy. The levels of inflammatory and oxidative mediators, such as superoxide dismutase (SOD), tumor necrosis factor-α (TNF-α), catalase, reduced glutathione, and thiobarbituric acid reactive substances (TBARS), were estimated. In addition, the level of nerve growth factor (NGF) was estimated at the end of the study in different groups. The anti-NGF treatment decreased its upregulation in the dorsal root ganglion significantly. The results showed that isoeugenol, eugenol, and their combination have therapeutic potential against neuronal and oxidative damage induced by diabetes. In particular, both compounds significantly affected behavioral function in treated rats and showed neuroprotection against diabetic neuropathy, and their combination had synergistic effects.